Genitourinary syndrome of menopause. Issue 2 (June 2020) - Briggs, Paula
Genitourinary syndrome of menopause affects approximately 50% of women post-menopause and is under-reported. This review of the condition including established and newer treatment options aspires to empower clinicians to ask about symptoms and be more proactive in their management.